SCREEN-PRINTED ELECTRODES MADE ON STONE PAPER SUBSTRATE FOR URIC ACID ELECTROCHEMICAL DETECTION - VARODI, Codruța; POGĂCEAN, Florina; GHEORGHE, Marin; BARBU-TUDORAN, Lucian; PRUNEANU, Stela (Studia Universitatis Babeș-Bolyai Chemia, 2020)
Flexible screen-printed electrodes on stone paper substrate (HP) and modified with gold nanoparticles (HP-AuNPs) or AuNPs-poly-methylene blue (HP-AuNPs-PMB) were fabricated and morphologically investigated by SEM/EDS. The electrochemical properties of the new electrodes were studied by cyclic voltammetry (CV). The best electrocatalytic properties for uric acid detection were obtained with HP-AuNPs electrode: 0.16 µM Limit of Detection, 5x10-7- 10-4 M linear range and 20.7 mA/M sensitivity.